A Brief Review of Blue- and Bilberries’ Potential to Curb Cardio-Metabolic Perturbations: Focus on Diabetes - Carmen Crespo, M.; Visioli, Francesco (Current Pharmaceutical Design, 2017)
Some epidemiological studies suggest that increased consumption of anthocyanins is associated with lower risk of cardiovascular disease (CVD) and hypertension. Also, high consumption of anthocyanin-rich fruit, such as berries, is associated with a lower risk of developing type 2 diabetes (T2D). In this review, we briefly yet critically assess the available evidence in support of an anti-diabetic role of anthocyanins derived from berries, especially bilberry (Vaccinium myrtillus L., also known as European blueberry, whortleberry, huckleberry and blaeberry) and blueberry (Vaccinium corymbosum, native to the United States). Further, cellular and molecular mechanisms are discussed and the “pharma-nutrition” use of anthocyanin-based preparations for the prevention and treatment of T2D is examined. We conclude that animal and in vitro studies strongly indicate that bilberry and blueberry have the potential to ameliorate T2D and its cardio-metabolic outcomes. However, appropriate clinical trials are lacking and will eventually clarify whether these foods (either as such or formulated as nutraceuticals) might be added to the current pharma-nutritional armamentarium.
Keywords: nutraceuticals